Prevalence of beta thalassemia mutations in population of Gujarat using amplification-refractory mutation system–polymerase chain reaction - Gadhia, Pankaj K.; Vaniawala, Salil N.; Kachhadiya, Tushar B. (International Journal Of Community Medicine And Public Health, 2019)
Background: Beta thalassemia is the most common genetic disorder in India. Its trait, coinheritance and mutations vary from mild to severe condition, resulting in thalassemia minor (heterozygous), intermediate and major depending upon many factors. The objective of this study was to find out the prevalence rate and the carrier of beta thalassemia in population of Gujarat using molecular genetic analysis of beta thalassemia patients by targeted mutation assay (ARMS-PCR). Methods: A total 105 samples for beta thalassemia were analysed for IVS 1-5 (G→C) and CD 15 (G→A) mutations. These two common mutations of thalassemia in Gujarat were carried out using amplification refractory mutation system–polymerase chain reaction (ARMS-PCR) and gel electrophoresis method. Results: A total 105 samples referred to us for molecular genetic analysis. The occurrence of positive mutations of IVS 1-5 (G→C) and CD 15 (G→A) were found in 48 and 15 samples respectively. The rest were negatives. Conclusions: Present study concludes that the prevalence rate of Beta thalassemia was widespread among the Gujarat population. The identification of IVS 1-5 (G→C) and CD 15 (G→A) mutations was carried out. The analysis revealed that, mutational patterns of IVS 1-5 (G→C) was the most frequent among other mutations in Gujarat region.